Pelviureteric junction obstruction of the ipsilateral kidney caused by hydronephrosis secondary to crossed fused renal ectopia - Taiki Kato; Maria Aoki; Koei Torii; Takashi Hamakawa; Hidenori Nishio; Kentaro Mizuno; Yosuke Ikegami; Tetsuji Maruyama; Yutaro Hayashi; Takahiro Yasui (IJU Case Reports, 2022)
Introduction Crossed fused renal ectopia is rare and usually asymptomatic. However, it is associated with urological anomalies. Case presentation A 15‐year‐old Japanese boy was transported to our hospital with right abdominal pain and hematuria after a soccer ball hit his right abdomen. Computed tomography revealed right hydronephrosis beyond the center of the body and no left kidney. Percutaneous nephrostomy was performed immediately, and a pyeloplasty was scheduled for 5 months later. Right hydronephrosis was noted to have been caused by left pelvic expansion due to a crossed fused ectopic kidney (secondary to a left pelviureteric junction obstruction). Subsequently, a left dismembered pyeloplasty was performed. Twenty‐four months later, pain and hematuria were absent, and the creatinine level was 1.1 mg/dL. Ultrasonography revealed a shrunken right kidney. Conclusion We encountered a unique urological anomaly with crossed fused renal ectopia. Comprehensive anatomical evaluation before surgery is important for maintaining long‐term renal function.